Predictors of health behaviours among Indian college students: an exploratory study. Issue 2 (22nd June 2020) - Chawak, Shweta; Chittem, Mahati; S, Aswini; Varghese, Daigy; Epton, Tracy
Abstract : Purpose: The purpose of this study is to understand the association between health behaviours of diet, physical activity, smoking cigarettes, alcohol consumption, safe sex and sleep quality with demographic (e.g. age, gender) and psychological (i.e. stress, self-esteem and sense of coherence) factors in Indian residential college students. Design/methodology/approach: Students studying for Bachelor of Technology at residential colleges in India were invited to complete an online questionnaire regarding their health behaviours, demographics and psychological variables. Each health behaviour was regressed onto demographic and psychological factors to determine which of them were associated with performing each behaviour. Findings: There was no clear pattern of predictors for the health behaviours overall. Self-esteem was related to healthy diet, being single was related to adequate sleep, higher parental income was related to safer sex and being older was related to more alcohol use and safer sex. Research limitations/implications: This study revealed that health education efforts may need to be designed for specific behaviours and correlates among Indian college students. Interventions regarding (1) healthy eating should target students with lower self-esteem, (2) sleep should target students in a relationship and (3) safer sex should target younger students and those from less affluent backgrounds. Originality/value: This research is one of the first attempts to study the predictors of health behaviours among Indian college students. The study highlighted that psychological factors (e.g. self-esteem) and demographic factors (e.g. relationship status, parental income, age) affect different health behaviours. These findings can help health educators to design tailored interventions and aid in health education and promotion among Indian college students.